Renovate or replace? Consequential replacement LCA framework for buildings - Satu Huuhka; Malin Moisio; Emmi Salmio; Arto Köliö; Jukka Lahdensivu (Buildings & Cities, 2023)
Is it more environmentally friendly to replace an existing building with a new one or to renovate the existing property? This paper addresses how to frame and evaluate this question. Although several previous studies exist, their methods lack a harmonised set of practice. A new framework is introduced that adopts the concept of consequential replacement framework (CRF) for life cycle assessment (LCA) which had previously been applied to vehicles. The application of the CRF to buildings is demonstrated with case studies on school buildings in Finland. Three alternative cases are examined: the refurbishment of a 1950s school; extending it with an annex; and demolition and replacement with a new concrete or timber building. As the European environmental impact regulation of buildings pertains to CO2 emissions, the paper also focuses on CO2. The case studies demonstrate that refurbishment in Finland is a more climate-friendly alternative to demolition and new build. The studied new buildings’ better energy efficiency is set off for decades by the carbon spike caused by the embodied CO2 in their materials. The CRF is shown to be a methodologically sound, easily approachable framework for evaluating immediate environmental consequences of decision-makers’ retention or replacement choices, suitable to different contexts. Policy relevance As the global CO2 budget is running out, the need to combat the escalation of the climate emergency is imminent. Decades-long payback times for embodied CO2 investments in new replacement buildings, as in the paper’s case studies, are not helpful in this effort. The introduced framework helps to uncover the climate change mitigation potential in building preservation, which is presently poorly understood and considered in policymaking. The new framework provides a useful decision support tool and evidence for both policymakers and planners. Current policy initiatives in Europe focus on CO2 regulation for new build and renovation. However, replacement situations are not yet regulated. In contexts where renovation clearly proves to be more climate friendly (as validated by this method), policymakers should recognise the greenhouse gas-mitigation potential in building retention and create policies to encourage renovation over new build.